PENGARUH KOMUNIKASI INTERPERSONAL DAN MANAJEMEN KONFLIK TERHADAP EFEKTIVITAS TIM KERJA KARYAWAN PADA PT CITA LINI PERSADA DI TANGERANG - Sugeng Riyadi; Shela Indah Savitri (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to determine the influence of interpersonal communication and conflict management on employee team effectiveness at PT Cita Lini Persada in Tangerang, both partially and simultaneously. The research employed a quantitative associative approach. The population consisted of 52 employees and the sample comprised 52 respondents selected using probability sampling with a simple random sampling method. Data were collected through questionnaires and analyzed using SPSS version 25 through validity and reliability tests, classical assumption tests, multiple linear regression, correlation analysis, coefficient of determination, t-tests, and an F-test. The results show that interpersonal communication has a positive and significant effect on team effectiveness (t = 2.290; p = 0.026), while conflict management also has a positive and significant effect (t = 5.444; p < 0.001). Simultaneously, interpersonal communication and conflict management significantly affect team effectiveness (F = 101.929; p < 0.001). The multiple regression equation is Y = 3.872 + 0.292X1 + 0.621X2, with R² = 0.806, indicating that both variables explain 80.6% of the variation in team effectiveness.